INVESTIGATING THE ROLE OF VOCABULARY PRE-TEACHING IN B2 READING COMPREHENSION - Mohlaroyim Shavkat qizi Karimova,Diyora Hoshimova (International Journal of Literature and Language Studies, 2026)
Reading comprehension is one of the most essential skills in foreign language learning, particularly at the B2 proficiency level where learners encounter increasingly complex academic and authentic texts. However, insufficient vocabulary knowledge often creates significant barriers to successful comprehension. This study investigates the effectiveness of vocabulary pre-teaching in enhancing reading comprehension among B2-level English as a Foreign Language (EFL) learners. The research was conducted among students of Namangan State Institute of Foreign Languages through a structured questionnaire designed to explore learners’ experiences, perceptions, and attitudes toward vocabulary pre-teaching practices. Quantitative findings indicate that vocabulary instruction prior to reading activities positively affects learners’ comprehension, confidence, motivation, and overall reading performance. The results reveal that pre-teaching key lexical items reduces cognitive load, facilitates text processing, and contributes to more effective engagement with reading tasks. The study highlights the pedagogical importance of integrating vocabulary pre-teaching into reading instruction and provides practical implications for EFL educators seeking to improve learners’ reading outcomes.